GENERAL STRUCTURE, TYPES AND FORMATS OF DIGITAL DATA OF REMOTE SENSING OF THE EARTH - Shaimerdenov , Д.М.; Закирова, А.Б. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
Earth remote sensing technologies (ERS) are an indispensable tool for the study and continuous monitoring of our planet, helping to effectively use and manage its resources. The modern development of remote sensing technologies expands the scope of their application, covering all aspects of our lives. This article describes the main stages of the development of remote sensing technologies, provides an overview of methods for observing elements of the environment, and considers the General structure, types and formats of digital data for remote sensing of the Earth. The main characteristics of aerospace survey data are defined, methods of storing coordinate reference data and data storage formats are considered. The main methods for representing geographical data are given, and the important qualities of each type of remote sensing data representation are described. The analysis of integration types to represent geographic data and identified the principal benefits of an integrated data view ERS.